2001
DOI: 10.1086/324710
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic—but Not Variant—Creutzfeldt-Jakob Disease Is Associated with Polymorphisms Upstream of PRNP Exon 1

Abstract: Human prion diseases have inherited, sporadic, and acquired etiologies. The appearance of the novel acquired prion disease, variant Creutzfeldt-Jakob disease (vCJD), and the demonstration that it is caused by the same prion strain as that causing bovine spongiform encephalopathy, has led to fears of a major human epidemic. The etiology of classical (sporadic) CJD, which has a worldwide incidence, remains obscure. A common human prion-protein-gene (PRNP) polymorphism (encoding either methionine or valine at cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 27 publications
5
75
4
Order By: Relevance
“…PRNP T1368C polymorphism was found to be associated with sCJD in UK (p = 0.003) and among 129Met/Met homozygotes in German study (p = 0.049). 12,15 However, no differences in genotype and allele frequencies between sCJD patients and controls were found in Korean populations. 16 This discrepancy may be related to the differencies in the ethnic background of the investigated populations or to different demographic structure.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…PRNP T1368C polymorphism was found to be associated with sCJD in UK (p = 0.003) and among 129Met/Met homozygotes in German study (p = 0.049). 12,15 However, no differences in genotype and allele frequencies between sCJD patients and controls were found in Korean populations. 16 This discrepancy may be related to the differencies in the ethnic background of the investigated populations or to different demographic structure.…”
Section: Discussionmentioning
confidence: 90%
“…These results in part confirm the previous study undertaken in British population by Mead et al who found decreased frequency of TC-AG genotype in sCJD compared with controls (5.4 vs. 22.3%). 12 Haplotype-based association analysis revealed that the distribution of C-G haplotype was significantly different between sCJD patients and controls. Our results are in contrast to the results reported by Jeong et al who showed no association of C-G containing haplotype (ht6) with CJD in Korean population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Codons 127 and 219 of PRNP also harbour amino-acid (AA) polymorphisms that confer resistance to Kuru 5 or sCJD. 6 Recently, other candidate genes have been identified as risk factors for sCJD, such as an SNP upstream of PRNP exon 1 (SNP 1368), 7 c.592C4T(p.T174M) in prion-like doppel gene (PRND), 8 APOE e4 allele, 9 polymorphisms at CALHM1 gene, 10 and BACE1 gene. 11 Identification of the potential genetic risk factors for sCJD seems to be one of the important pathways for understanding of the pathogenic mechanisms and human susceptibility to the disease.…”
Section: Introductionmentioning
confidence: 99%